Automated Measurement of Blood Pressure in Routine Clinical Practice - Myers, Martin G. (J Clin Hypertens (Greenwich), 2007)
In recent years, automated devices have been developed to record blood pressure (BP) accurately in the home and during usual daily activities. Clinical outcome studies have clearly shown home BP and 24‐hour ambulatory BP to be significantly better predictors of future cardiovascular events compared with BP recorded in the office setting using mercury sphygmomanometry. It is also now possible to measure office BP with the patient resting quietly alone in the examining room using an automated device. Studies in routine clinical practice using this approach have demonstrated that automated office BP can eliminate most of the white coat effect seen with manual BP measurement. The automated office BP also correlates significantly better than does the routine office BP with the 24‐hour ambulatory BP, the gold standard for predicting risk of future cardiovascular events. Sufficient evidence now exists to consider incorporating automated office BP into an algorithm for diagnosing hypertension.